Broadband photoluminescence of silicon nanowires excited by near-infrared continuous wave lasers. (1st February 2018) - Li, Zongbao; Wang, Xin; Liu, Shaojing; Yang, Jianxin; Shi, KeZhang; Wang, Haiyan; Zhu, Debin; Xing, Xiaobo
Highlights: Broadband photoluminescence of silicon nanowires excited using 980 nm continuous wave laser are showed. Same PL slope values confirmed positive proportional to the concentrations of emission photon numbers. The possible mechanism of hot luminescence are discussed. Abstract: In advanced nanomaterials field, silicon nanowires (SiNWs) play an increasing significant role due to the outstanding optical properties. Although various kinds of investigations for SiNWs in optical characteristic have been proposed, it remained rare study of the photoluminescence (PL) phenomenon. Here, we theoretically and experimentally demonstrate an upconversion PL with broadband spectrum by exciting SiNWs using 980 nm continuous wave laser. PL spectra are efficiently detected and range from 500 nm to 920 nm. An electron can be transferred to higher excitation energy levels by absorbing one photon with the assistance of multi-phonons, producing hot luminescence. The proposed concept of PL phenomenon can be extended to biosensor, fluorescence labeling systems, and miniature broadband optical source emitters.